Propuesta para implementar la mediación como medio de solución de controversias para casos de fijación de pensiones de alimentos y régimen de visitas - Castillo Toapanta, Ingrid Gabriela (2012)
This paper tries to implement titling Mediation as a means of dispute resolution incase of fixation of maintenance and visitation, for whish basic covering topics related to mediation, such as historical, doctrinal concepts, characteristics essential mediation role of the mediator and other related research. Sustaining the right you have children by their parents at the time of perceiving food and visits required by their parents